THE EFFECTS OCCURRED IN BLOOD PARAMETERS FOR NEWBORNS MATERNAL ADMINISTRATION WITH URANYL ACETATE - Alwachi, Sabah; Alkaisy, Kawkab; Kready, Hussein (Iraqi Journal of Science, 2024)
The aim of this research was to determine the effects in some blood parameters in the newborns after the maternal administration of Uranyl acetate.12 mature females, Swiss Albino rats were used. Animals were divided in to two main groups. The first group received, distilled water only and used as control. While the second group received daily Uranyl acetate orally (75 mg / kg b.w).The administration was done, from the first day of gestation, labor, lactation and then continuous fore four weeks’. The pops were subdivided in to two subgroups. The first was killed at the age of two weeks and the second was killed at age of four weeksThe following results were obtained.1 - A significant (P< 0.05) increase was found in the total WBC counts in the popsblood of the second group for two age stages.2 - A significant (P< 0.05) increase was observed in the WBC differential count (i.e. neutrophils) in the second group for two old stages. Also significant (P<0.05) decreases were found in the WBC differential count (i.e. lymphocytes) in the same subgroup mentioned above.